Savas miestas: asmens savasties aspektas. Utena Alfonso Nykos-Niliūno kūryboje - Šmitienė, Giedrė (Literatūra, 2015)
The paper is based on the concept of experiencing consciousness that embraces the experience expressed in the text and the lived pre-textual experience. The reversibility of the fiction and the experienced reality is investigated. The investigation discovers the map of the town constantly recurring in the poetry of Nyka-Niliūnas. This reconstructed map is identical to the native town of the poet. The town reveals itself in the poetry as the own lived town of the speaker. The same topography of the town is repeated in the diaries in the forms of the dreams as well as of the reminiscences. The special substrate of the speaking consciousness is evident. The interconnection between the three modes of consciousness – poetic, remembering and the dreaming – is exposed. All the three intensive forms of the consciousness deal with the personal identity. The recurrence of the space of the town is motivated and the perpetual return to the same space is clarified.